How mature-age students succeed in higher education: implications for institutional support. Issue 3 (4th May 2017) - Heagney, Margaret; Benson, Robyn
ABSTRACT: This article draws on stories of success in higher education by mature-age students of diverse backgrounds to highlight some key implications for institutional support. We begin by reviewing the post-World War II background of mature-age study in Australian higher education to provide a context for presenting some major findings from a small, in-depth research project. We examine these findings to focus on the role of institutional support in the success of mature-age students, particularly given recent sectoral factors affecting their access and support. The study findings show students' primary supports were families and friends. Participants all belonged to equity categories as designated by the Australian government, but many did not use institutional supports. Some lacked the confidence to approach staff; others were unaware support services existed or lacked the time to access them. The participants' stories demonstrate the complex disadvantages experienced by mature-age students. They highlight universities' need to ensure support services are 'student-centred' in order to ensure improved educational and equity outcomes for their mature-age student populations.